Silisyum dioksit depozisyon sistemi - Şekerkıran, Barbaros (Fen Bilimleri Enstitüsü, 1992)
Yapılan çalışma, iki inçlik silisyum pul üzerinde kimyasal buhar yoğuşturma metoduyla katkılı ve katkısız silisyum di oksit film oluşturacak bir depozisyon sisteminin tasarım ve gerçeklenmesidir. Araştırma amaçlı çalışmalarda kullanılacak sistem bir seferde tek pul işleyecektir. İlk etapta katkısız film oluşturulması hedeflenmişse de, sistem katkı gazlarının eklenmesiyle katkılı filmler oluşturacak şekilde tasarlanmıştır. Sozkonusu filmler, yarıiletken teknolojisinde, pasivasyon, mas_ keleme, yalıtım, amacıyla kullanılabildikleri gibi difüzyon işlemlerinde katkı kaynağı görevi de görebilirler. Sistemin tasarımında, emniyet, güvenilirlik, raaliyet, film kalitesi ve kolay kullanım kriterleri göz önüne alınmıştır. Emniyet açısından, sistemin deneyimli kişiler tarafından kullara İması ve yalnız çalışılmaması önerilir.

This work consists of the design and the realiza_ t i on of an atmospheric pressure chemical vapor deposi_ tion reactor. Despite the fact that all the arrange_ merits are made in order to obtain undoped silica films, both phosphosilica glass and borphosphosilica glass films can be deposited by adding phosphpine and diboran. The system has all the gas and electrical connections for one type of dopant but. it can be easily modified to add second dopant source. This kind of films are of prime importance in solid state technology. They can be used as passivation layer, isolation layer between two conductor films, dopant source for diffusion process and masking layer. Reliabilty, cost, feasibility and film quality are the key criterions in designing this reac_ tor. The system must be used by experienced persons. Chemical vapor deposition is defined as the forma_ tion of a solid film on a substrate by reaction of vapor phase chemicals Creactants5 that contain the required constituents. These reactant gases are introduced into a reaction chamber and are decomposed and reacted at a heated surface to form the thin film. A wide variety of thin films utilized in VLSI fabrication is prepared by CVD. Specific deposition methods are developed to form such thin films, based on their potential capabilities for satisfying demanding criteria. CVD processes are often selected over competing deposition techniques be_ cause they offer the following advantages: a? high pur_ ity films can be achieved W a great variety of chemical compositions can be deposited c:> some films cannot be deposited with adequate film properties by any other methods d3 good economy and process control are possible in many cases.
Silicon dioxide deposition system
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1992
Keywords: Depozisyon sistemi; Kimyasal buhar çöktürme; Silisyum dioksit; İnce filmler; Deposition system; Chemical vapor deposition; Silicon dioxide; Thin films